424 Considerations Mid-Translation of a Novel Extracellular Vesicle Product in Myocarditis. (April 2022) - Beetler, Danielle; Bruno, Katelyn A.; Behfar, Atta; Cooper, Leslie T.; Fairweather, DeLisa
Abstract : OBJECTIVES/GOALS: Myocarditis is an inflammatory cardiomyopathy commonly caused by viral infections. The residual burden of this disease after guideline-based therapies is substantial, as there are no pathway-specific therapies. Our long-term goal is to find and translate treatments that reduce acute myocarditis severity and prevent progression of disease. METHODS/STUDY POPULATION: Of available therapies, extracellular vesicles (EVs) are ideally suited to the task of simultaneous, specific reprogramming of multiple pathogenesis mechanisms necessary in diseases like myocarditis, without similar immunosuppressive risks as their pharmacologic counterparts. We obtained plasma from healthy men and women and isolated nanoparticles, which were analyzed for physiochemical markers of human EVs. After confirming presence of EVs, we injected these plasma-derived extracellular vesicles (PEV) into male BALB/c mice vs. PBS control intraperitoneally on days -1, 0, 1 of viral infection (day 0) in a highly translational, mouse model of myocarditis. Hearts were examined at day 10 at the peak of acute myocarditis, using standard histological and cell composition analyses. RESULTS/ANTICIPATED RESULTS: Mice treated with PEV had significantly less myocardial inflammation both histologically and by gene expression of immune markers in the heart. The immunoregulation by PEV treatment decreased many key components of innate immune response networks that are known to be upregulated during acute myocarditis: TLR4+ mast cells and macrophages and complement. These pathways drive the profibrotic gene and protein changes that lead to remodeling, fibrosis, and disease progression observed in patients. We anticipate that when we analyze later timepoints in this model (day 35 post infection) which are normally associated with development of chronic myocarditis, dilated cardiomyopathy, we will see reduction of this fibrosis and of damage-associated changes. DISCUSSION/SIGNIFICANCE: These data suggest that EVs from plasma may be a novel treatment for viral myocarditis, but translation of EVs is hindered by their heterogeneity. We demonstrate characterization both physiochemically and functionally in a well-defined model. Such practices are necessary as these contemporary products challenge current regulation standards.